The Tourism Office's strategy in maintaining Bendi which has changed its function as a cultural identity in Jam Gadang Kota Bukittinggi - Rahmi, Rahmida Gusnizar; Endrizal; Mutia Kahanna (Kirana Publisher (KNPub), 2023)
This study discusses the strategy used by the Bukittinggi City Tourism Office towards bendi as cultural transportation. The purpose of this study is to explain the changes in the function that occurred in bendi from the Dutch colonial era until now and the strategies carried out so that this bendi tourism can survive until now. The research method used is qualitative research. Data collection techniques include field observations, interviews, and documentation. The theory used is Talcott Parson's theory of Modernization and the Theory of Change by John Lewis Gillin. The finding of this study is that bendi underwent a change in function, bendi was originally the main transportation used by the ruler because at that time bendi was the only mainstay transportation. The progress of science and technology gradually resulted in vehicles becoming varied so that bendi became public vehicles that all people could ride. The development of technology, making bendi no longer a public transportation but converted into cultural transportation used by the Bukittinggi Tourism Office to become a mainstay tourism. The strategy offered by the Bukittinggi City Tourism Office in maintaining bendi is to provide training to bendi coachmen, deworming to bendi horses, provide decorative lights, brand signs, and uniforms, then number the bendi, and finally the base site determination.